FORMULATION OF PGV-0 A NEW ANTIINFLAMMATORY AGENT AS A TABLET DOSAGE FORM - Oetari, R. A.; ., Sardjiman; Yuwono, Tedjo; Fudholi, Achmad (Indonesian Journal of Pharmacy, 2003)
The specific objective of this study is to get the best formulation for PGV-0 as a tablet dosage form. By optimation of formulation a more potent and safe antiinflamatory drug could be obtained. This study was started with determination of physical properties which included: appearance, particle size, partition coefficient, and hygroscopicity. In the formulation of PGV-0 6 formulas were chosen with amylum and lactose as fillers, tween 80 as surfactant, solutiogelatine and solutio PVP as binding agent and talc and Mg stearate as lubricants. From these six formulas chosen physical properties of the granules and tablets were determined. PGV-0 powder was not free flowing and has bad compressibility. PGV-0 could not be proccesed by direct compression but should be formulated by wet granulation method. The best formula found was formula V which used solutio PVP 2 % as binding agent and tween 80 0,25 % as wetting agent.Key words: PGV-0, antiinflammation, formulation of tablet dosage form.